The Program and Treatment Effect of Summer Jobs on Girls' Post-Schooling Incomes. (June 2015) - Alam, Moudud; Carling, Kenneth; Nääs, Ola
Background: Public programs offering summer jobs to smooth the transition from school to work is commonplace. However, the empirical support for summer jobs is limited. This article exploits the availability of registered individual information and random allocation to summer jobs to provide empirical evidence on this issue. Objectives: To identify the effect of summer job programs on the post-schooling incomes of the intended participants. Also to identify the effect of sophomore girls' high school work experience on their post-schooling incomes. Research Design: In this article, 1, 447 sophomore girls from 1997 to 2003 are followed 5–12 years after graduation. They all applied to Falun municipality's (Sweden) summer job program, and about 25% of them were randomly allotted a job. The random allocation to a summer job is used to identify the causal effect of sophomore girls' high school income on their post-schooling incomes. Subjects: All the 1, 447 sophomore girls who applied to Falun municipality's summer job program during 1997–2003. Measures: Annual post-schooling income is used as an outcome measure. The work experience of girls in high school is also measured in terms of total income while in high school. Results: The program led to a substantially larger accumulation of income during high school as well as 19% higher post-schooling incomes. The high school income led to a post-schooling income elasticity of 0.37 which is, however, potentially heterogeneous with regard to academic ability. Conclusions: Both the program effect and the causal effect of high school income on post-schooling incomes were substantial and statistically significant.